Pengaruh Penggunaan Teknologi Digital dan Motivasi Terhadap Prestasi Akademik Siswa di MA-YA Ikhsan Kabupaten Pasuruan - Alfiatur Rohmah; Sugeng Pradikto (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to analyze the effect of the use of digital technology and learning motivation on students' academic achievement at MA-YA Ikhsan, Pasuruan Regency. In today's digital era, technology has become an important component in the learning process, which can increase interaction between students and subject matter. The method used in this study is quantitative, involving 30 students randomly selected from the school population. Questionnaires were distributed to students to collect data on the frequency of digital technology use, level of learning motivation, and students' academic achievement. The results showed that 80% of students often use digital technology routinely to learn, and 70% of them feel more motivated when learning with digital media. The average academic score of students who actively use technology reaches 85, while students who are not active only reach 75. These findings indicate a significant positive relationship between the use of digital technology and learning motivation on students' academic achievement. Therefore, it is important for schools to continue to integrate technology into the learning process in order to improve the quality of education. Through this study, it is hoped that educators can understand the importance of utilizing technology in learning and creating an environment that supports student motivation. This research can also be a reference for further studies on the impact of technology in education in various contexts.